Implications of deferred diagnosis of paediatric intracranial germ cell tumours. Issue 3 (29th December 2022) - Partenope, Cristina; Pozzobon, Gabriella; Weber, Giovanna; Carceller, Fernando; Albanese, Assunta
Abstract: Aims: This study analysed the clinical features of a cohort of children with intracranial germ cell tumours (IC‐GCTs). We retrospectively reviewed timelag between symptoms onset, clinic‐radiological findings, diagnosis and outcomes. Methods: Symptoms at diagnosis were divided into four groups: (1) raised intracranial pressure (RICP); (2) visual impairment; (3) endocrinopathies; (4) other. Total diagnostic interval (TDI), defined as the interval between symptom onset (including retrospective recall of symptoms) and definitive diagnosis of IC‐GCT, was calculated and compared to survival rates. Results: Our cohort included 55 children with median follow‐up of 78.9 months (0.5–249.9). The majority (63.6%) had germinomas and 10.9% were metastatic at diagnosis. IC‐GCTs were suprasellar (41.8%), pineal (36.4%), bifocal (12.7%) or in atypical sites (9.1%). The most common presenting symptoms were related to RICP (43.6%); however, by the time of tumour diagnosis, 50.9% of patients had developed endocrine dysfunctions. All pineal GCTs manifested with RICP or visual impairment. All suprasellar GCTs presented with endocrinopathies. TDI ranged between 0.25 and 58.5 months (median 4 months). Pineal GCTs had the shortest TDI (median TDI 1 month versus 24 months in suprasellar GCTs, p  < .001). TDI > 6 months was observed in 47.3% of patients and was significantly associated with endocrine presenting symptoms. No statistically significant difference was found in progression‐free survival and overall survival between patients with TDI > 6 months and with TDI ≤ 6 months. Conclusion: Approximately half of the IC‐GCT patients in this cohort had TDI > 6 months. These presented mostly with endocrine deficits. TDI > 6 months was not associated with increased relapse or mortality rates.